Synonymy of two important crop pests of burrower bugs, Cyrtomenus mirabilis and C. bergi (Hemiptera: Cydnidae), based in a multi-source approach - Avendaño, José Mauricio; Barão, Kim Ribeiro; Grazia, Jocelia; Schwertner, Cristiano Feldens (Zootaxa, 2018)
Burrower bugs are unique among true bugs, recognized by the morphological adaptations for digging, and include several species of economic importance for causing damages in roots and ground pods. Damage records has been growing in the last two decades in the Neotropics, but taxonomic problems still hampers studies in these group of insects. Cyrtomenus bergi Froeschner and C. mirabilis (Perty), species of economic interest and widely distributed in the Neotropics, have no clear morphological differentiation raising doubts about the correctness of identifications made to date, even validity of these species. Taxonomic problems, as species delimitation and identification, can benefit from different approaches, bringing tools and complementary information for establishing a species status. In this work, we use the different sources (morphology, distribution, linear and geometric morphometric), to access the identity of C. bergi and C. mirabilis and define the recognition of both as separated species. Results shows overlapping of geographical distribution and lack of quantitative and qualitative morphological differences, supporting C. bergi as a junior synonym of C. mirabilis; studies about this important pest species should consider only the latter as valid species.